THE CONCEPT OF INSAN KAMIL AND ITS RELEVANCE TO THE SPIRITUAL BELIEFS OF GENERATION Z: INSIGHTS FROM IBN ARABI - Naufal Siregar, Adnan Faris; Bustam, Betty Mauli Rosa (Hunafa: Jurnal Studia Islamika, 2024)
The aim of this research is to answer the problems of human character. Approach to human character which has been degraded from various dimensions, the moral degradation that occurs is not without cause, but because there are many things in the soul that have not grown perfectly in its formation. This research is qualitative research using the library method. The research results show that Ibn Arabi's concept of insan kamil emphasizes the achievement of human perfection through the manifestation of divine qualities. Its implementation for generation Z includes strengthening self-concept, sustainable personality development, and balancing material-spiritual aspects. Moral education based on Ibn Arabi's thoughts aims to form noble morals by combining modern education and Sufism values. This research finds the relevance of Ibn Arabi's thoughts in the development of spirituality and moral education for the younger generation in the contemporary era.especially generation Z, can achieve Insan Kamil through the process of Spirituality.